Nexsus Between Foreign Policy and Institutional Functions: The Case of Pakistan - Tariq, Muhammad; Khan, Muhammad Fahim; Rasheed, Muhammad Ijaz; Ahmad , Munir (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
Foreign policy is the program that structures how a state maintains its relations with other states in international society. In the 21stcentury globalized world, the implication of foreign policy of a state for its survival and well- being has increased many folds. Since foreign policy is made ad executed by certain state institutions, it has a direct bearing on internal and external functions of the state. This article attempts to elaborate the nexus between foreign policy and the functions of state institutions. Building on a descriptive and analytical methodology, this article suggests that there is a direct link between institutional functioning and the formulation and execution of foreign policy, that is, the weaknesses and strengths in one realm affect the effectiveness of the other. It is therefore recommended here that governments must strengthen domestic institutional structures and should contribute to the formation of a strong institutional culture in order to safeguard their foreign policy objectives.